ISO 9001:2015 Quality Management System Implementation To Improve the Performance of Vocational High Schools in Sumedang Regency, West Java Province - Erwin Firdaus; Trisnamansyah, Sutaryat; Warta, Waska; Tejawiani, Ida (International Journal of Educational Research & Social Sciences, 2022)
The background of this research is that the achievement of the school's vision, mission and goals is highly dependent on school leadership and optimization of teacher performance through good management. This study aims to describe the implementation of the ISO 9001:2015 Quality Management System which includes the stages of the program plan, implementation of the action plan, and follow-up in improving school performance. The research uses a qualitative approach through the case study method. Sources of data were collected using observation, interview, documentation, and a mixture of the three techniques. The research location is in State Vocational High School 1 and State Vocational High School 2 Sumedang Regency, West Java Province. The conclusions of the research are as follows: (a) The school has implemented the ISO 9001:2015 Quality Management System in a well-planned, detailed and well-planned manner so that it has an impact on school performance; (b) The principal's leadership looks visionary, looks firm, patient and diligent in dealing with the problems faced by the school; (c) The system and process approach is carried out by both schools through a quality management system; (d) Schools make good program plans, action plans, follow-up plans, have a school-level ISO organization team; and (e) Several obstacles and complaints related to teacher performance can be followed up by evaluation in management review. Thus, further research is still needed related to the effectiveness of financial governance and the achievement of graduate competency standards.